Heterobimetallic [NiFe] complexes containing mixed CO/CN− ligands: analogs of the active site of the [NiFe] hydrogenases - Perotto, Carlo U.; Sodipo, Charlene L.; Jones, Graham J.; Tidey, Jeremiah P.; Blake, Alexander J.; Lewis, William; Davies, E. Stephen; McMaster, Jonathan; Schröder, Martin (American Chemical Society, 2018)
The development of synthetic analogs of the active sites of [NiFe] hydrogenases remains challenging and, in spite of the number of complexes featuring a [NiFe] center, those featuring CO and CN− ligands at the Fe center are under-represented. We report herein the synthesis of three bimetallic [NiFe] complexes [Ni(N2S2)Fe(CO)2(CN)2], [Ni(S4)Fe(CO)2(CN)2] and [Ni(N2S3)Fe(CO)2(CN)2] that each contain a Ni center that bridges through two thiolato S donors to a {Fe(CO)2(CN)2} unit. X-ray crystallographic studies on [Ni(N2S3)Fe(CO)2(CN)2], supported by DFT calculations, are consistent with a solid state structure containing distinct molecules in the singlet (S = 0) and triplet (S = 1) states. Each cluster exhibits irreversible reduction processes between −1.45 to −1.67 V vs Fc+/Fc and [Ni(N2S3)Fe(CO)2(CN)2] possesses a reversible oxidation process at 0.17 V vs Fc+/Fc. Spectroelectrochemical infrared (IR) and electron paramagnetic resonance (EPR) studies, supported by density functional theory (DFT) calculations, are consistent with a NiIIIFeII formulation for [Ni(N2S3)Fe(CO)2(CN)2]+. The SOMO in [Ni(N2S3)Fe(CO)2(CN)2]+ is based on Ni 3dz² and 3p S with the S contributions deriving principally from the apical S-donor. The nature of the SOMO corresponds to that proposed for the Ni-C state of the [NiFe] hydrogenases for which a NiIIIFeII formulation has also been proposed. A comparison of the experimental structures, and the electrochemical and spectroscopic properties of [Ni(N2S3)Fe(CO)2(CN)2] and its [Ni(N2S3)] precursor, together with calculations on the oxidized [Ni(N2S3)Fe(CO)2(CN)2]+ and [Ni(N2S3)]+ forms suggests that the binding of the {Fe(CO)(CN)2} unit to the {Ni(CysS)4} center at the active site of the [NiFe] hydrogenases suppresses thiolate-based oxidative chemistry involving the bridging thiolate S donors. This is in addition to the role of the Fe center in modulating the redox potential and geometry, and supporting a bridging hydride species between the Ni and Fe centers in the Ni-C state..